PERUNDINGAN BIPARTIT SEBAGAI LANGKAH AWAL DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - I Nyoman Jaya Kesuma; I Wayan Agus Vijayantera (Jurnal Hukum Saraswati (JHS), 2020)
The bipartite negotiation is the first attempt taken to resolve industrial relations problems that occur. Therefore it is interesting to conduct an in-depth analysis of the importance of conducting bipartite negotiations in the resolution of industrial relations disputes and the existence of collective agreements as a legal basis for implementing bipartite negotiation agreements. Bipartite negotiations as an initial effort to settle industrial relations disputes require good faith in the negotiation process, the formation of collective agreements, and the implementation of collective agreements. Carefulness and caution are also needed in the formulation of collective agreements so that agreement clauses not cause in losses or problems in implementation.